Memahami Dasar Perkalian bagi Mahasiswa Calon Guru MI/SD - Abidah, Faizah Nurul (Maliki Interdisciplinary Journal, 2024)
Knowing the Understanding of Madrasah Ibtidaiyah or Elementary School Teachers' Understanding of the Concept of Multiplication through Problem Posing. Explaining that this research aims to comprehensively identify students' mistakes regarding the concept of multiplication and provide recommended learning designs in instilling or constructing the concept of multiplication. This research uses types of initial algebra learning difficulties as a basis. The research results show that for elementary school teachers or prospective elementary school teachers, there are three steps to understanding the concept of multiplication, I understand the concept of multiplication as a whole, I don't understand the concept of multiplication. This research also emphasizes the importance of students' knowledge and understanding of the subjects taught at Madrasah Ibtidaiyah or Elementary Schools.